Gender and Age differences in Leukaemia among Children in Tripoli University Hospital - Hisham Yousuf Mousay (AlQalam Journal of Medical and Applied Sciences, 2025)
Leukemia accounted for approximately 2.5% of all new cancer incidence and 3.1% of cancer-related mortality. The investigation of its risk factors and epidemiologic trends could help describe the geographical distribution and identify high-risk population groups. Thus, we examine the leukemia epidemiology and risk factors in children attended the University Hospital of Tripoli. A retrospective cross-sectional study was carried out based on patients’ data which was obtained from the University Hospital of Tripoli for the period of Jan to Dec 2024. We extracted variables included age, gender, ethnicity, family history, and investigation from the hospital record. Data were analyzed using mean ± standard deviation of mean and percentages. Microsoft excels were used as a software to run the analysis. It was observed that, out of 182 cases, 140 (76.9%) were male and 42 (23.1%) were females which indicates male predominance in all types of leukemia. The median age of male was 5.6±2 while the median age of female was 8.3±1. Complete blood count results show increase in white blood cell count above normal level in both males and female (range 21.1×109/L). The analysis of cancer incidence rates could provide important information about risk factors and potential changes that could aid in the discovery of ways to reduce the incidence of cancer in infants. شكلت اللوكيميا ما يقرب من 2.5٪ من جميع حالات الإصابة بالسرطان الجديدة و 3.1٪ من الوفيات المرتبطة بالسرطان. يمكن أن يساعد التحقيق في عوامل الخطر والاتجاهات الوبائية في وصف التوزيع الجغرافي وتحديد مجموعات السكان المعرضة للخطر. وبالتالي، فإننا نفحص وبائيات اللوكيميا وعوامل الخطر لدى الأطفال الذين حضروا إلى مستشفى طرابلس الجامعي. أجريت دراسة مقطعية استرجاعية بناءً على بيانات المرضى التي تم الحصول عليها من مستشفى طرابلس الجامعي للفترة من يناير إلى ديسمبر 2024. استخرجنا المتغيرات بما في ذلك العمر والجنس والعرق والتاريخ العائلي والتحقيق من سجل المستشفى. تم تحليل البيانات باستخدام متوسط ​​± الانحراف المعياري للمتوسط ​​والنسب المئوية. تم استخدام Microsoft Excels كبرنامج لتشغيل التحليل. لوحظ أنه من بين 182 حالة، كان 140 (76.9٪) من الذكور و 42 (23.1٪) من الإناث مما يشير إلى غلبة الذكور في جميع أنواع اللوكيميا. كان متوسط ​​عمر الذكور 5.6 ± 2 بينما كان متوسط ​​عمر الإناث 8.3 ± 1. تظهر نتائج تعداد الدم الكامل زيادة في عدد خلايا الدم البيضاء فوق المستوى الطبيعي لدى كل من الذكور والإناث (نطاق 21.1 × 109 / لتر). يمكن أن يوفر تحليل معدلات الإصابة بالسرطان معلومات مهمة حول عوامل الخطر والتغيرات المحتملة التي يمكن أن تساعد في اكتشاف طرق للحد من الإصابة بالسرطان عند الرضع